Wettability-independent critical heat flux during boiling crisis in foaming solutions. (November 2018) - Raza, Md. Qaisar; Kumar, Nirbhay; Raj, Rishi
Graphical abstract: Highlights: CHF mechanism during pool boiling with aqueous surfactant solutions is explained. Multiple smaller bubbles (foam) with small rise velocity crowd the heater surface. Vapor crowding inhibits the supply of liquid to the heater, resulting in dryout. Premature CHF renders wettability improvements ineffective for CHF enhancement. CHF is modeled and validated over a wide range of concentrations. Abstract: We present the first experimental study of surface wettability-independent critical heat flux (CHF) during boiling crisis with foaming solutions. Foaming solution refers to those aqueous surfactant solutions, which are very effective in avoiding bubble coalescence and form vapor foam. The slowly rising small bubbles in the foam crowd the heater surface to inhibit rewetting and trigger boiling crisis. Similar to the typical relation between the terminal velocity and the bubble size, we observe a power law exponent of half between the CHF and the bubble size. Such a behavior suggests that the ability of buoyancy to remove bubble swarm away from the heater surface dictates the CHF during boiling with foaming solutions. Resulting premature dryout not only reduces CHF significantly in comparison to boiling with pure water but also renders the effect of wettability improvements from micro-/nano- texturing inconsequential to CHF enhancement. Terminal velocity of the rising bubbles is estimated to model the maximum vapor-removal capacity and successfully predict the CHF over a wide range of concentrations. We further show that weakly foaming surfactants, or, the strongly foaming surfactants, but at lower concentrations, behave similar to water wherein they form large bubbles and wettability improvements via surface modifications exhibit CHF enhancements. The physical insights gained in this study can now be used to devise strategies for CHF enhancement with aqueous surfactant solutions.